Nano-SiC-decorated Y2Si2O7 ceramic for enhancing electromagnetic waves absorption performance. Issue 14 (15th July 2022) - Wang, Cunxian; Chen, Lianyang; He, He; Ye, Tian; Deng, Qiong; Wei, Hanjun; Zhao, Feng; Wang, Qingyuan
Abstract: To improve the electromagnetic (EM) wave absorption performance of rare earth silicate in harsh environments, this work synthesized dense SiC–Y2 Si2 O7 composite ceramics with excellent EM wave absorption properties by using the polymer permeation pyrolysis (PIP) process, which introduced carbon and SiC into a porous Y2 Si2 O7 matrix to form novel composite ceramics. SiC–Y2 Si2 O7 composite ceramics with different numbers of PIP cycles were tested and analysed. The results show that the as-prepared composites exhibit different microstructures, porosities, dielectric properties and EM wave absorption properties. On the whole, the SiC–Y2 Si2 O7 composite ceramics (with a SiC/C content of 29.88 wt%) show superior microwave absorption properties. The minimum reflection loss (RLmin ) reaches −16.1 dB when the thickness is 3.9 mm at 9.8 GHz. Moreover, the effective absorption bandwidth (EAB) included a broad frequency from 8.2 GHz to 12.4 GHz as the absorbent thickness varied from 3.15 mm to 4.6 mm. In addition, the EM wave absorption mechanism was analysed profoundly, which ascribed to the multiple mediums of nanocrystalline, amorphous phases and turbostratic carbon distributed in the Y2 Si2 O7 matrix. Therefore, SiC–Y2 Si2 O7 composite ceramics with high-efficiency EM wave absorption performance promise to be a novel wave absorbing material for applications in harsh environments.